2019
DOI: 10.3390/nu11071680
|View full text |Cite
|
Sign up to set email alerts
|

Food and Nutrient Intake during Pregnancy in Relation to Maternal Characteristics: Results from the NICE Birth Cohort in Northern Sweden

Abstract: Linkages between diet and other lifestyle factors may confound observational studies. We used cluster analysis to analyze how the intake of food and nutrients during pregnancy co-varies with lifestyle, clinical and demographic factors in 567 women who participated in the NICE (nutritional impact on immunological maturation during childhood in relation to the environment) birth-cohort in northern Sweden. A food frequency questionnaire, Meal-Q, was administered in pregnancy Week 34, and the reported food and nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 26 publications
10
38
0
Order By: Relevance
“…The latter explanation is supported by previous research suggesting that these symptoms are associated with a higher intake of soft drinks and a deterioration in dietary quality [24,25]. The nutrient intake in the current study is similar to the intake in a recent study using the same FFQ among pregnant women in the north of Sweden [17].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The latter explanation is supported by previous research suggesting that these symptoms are associated with a higher intake of soft drinks and a deterioration in dietary quality [24,25]. The nutrient intake in the current study is similar to the intake in a recent study using the same FFQ among pregnant women in the north of Sweden [17].…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, very few data are available on nutritional intake among pregnant women in Sweden. Previous studies have found that reported dietary intake among pregnant Swedish women is of poor quality [16], with a low intake of many nutrients [17]. Neither of the previous studies have investigated associations between diet and GWG.…”
Section: Introductionmentioning
confidence: 98%
“…The association of dietary patterns with socioeconomic and other behaviors was consistent with results from other studies of dietary patterns of young pregnant or non-pregnant women [43][44][45]. Consumption of fruits, vegetables, whole grains, and fish was high in women with increased education [43,45].…”
Section: Discussionsupporting
confidence: 88%
“…Aging is associated with the lowering of Se levels [52]; however in the present study, women aged 18-45 were evaluated and statistically positive relationships between maternal age and Se levels were found. It means that other factors can also affect these correlations, e.g., diet or hormonal factors [65].…”
Section: Discussionmentioning
confidence: 99%